The nucleoside diphosphate kinase NDK‐1/NME1 promotes phagocytosis in concert with DYN‐1/Dynamin. Issue 10 (17th July 2019) - Farkas, Zsolt; Petric, Metka; Liu, Xianghua; Herit, Floriane; Rajnavölgyi, Éva; Szondy, Zsuzsa; Budai, Zsófia; Orbán, Tamás I.; Sándor, Sára; Mehta, Anil; Bajtay, Zsuzsa; Kovács, Tibor; et al.
ABSTRACT: Phagocytosis of various targets, such as apoptotic cells or opsonized pathogens, by macrophages is coordinated by a complex signaling network initiated by distinct phagocytic receptors. Despite the different initial signaling pathways, each pathway ends up regulating the actin cytoskeletal network, phagosome formation and closure, and phagosome maturation leading to degradation of the engulfed particle. Herein, we describe a new phagocytic function for the nucleoside diphosphate kinase 1 (NDK‐1), the nematode counterpart of the first identified metastasis inhibitor NM23‐H1 (nonmetastatic clone number 23) nonmetastatic clone number 23 or nonmetastatic isoform 1 (NME1). We reveal by coimmunoprecipitation, Duolink proximity ligation assay, and mass spectrometry that NDK‐1/NME1 works in a complex with DYN‐1/Dynamin ( Caenorhabditis elegans /human homolog proteins), which is essential for engulf ment and phagosome maturation. Time‐lapse microscopy shows that NDK‐1 is expressed on phagosomal surfaces during cell corpse clearance in the same time window as DYN‐1. Silencing of NM23‐M1 in mouse bone marrow—derived macrophages resulted in decreased phagocytosis of apoptotic thymocytes. In human macrophages, NM23‐H1 and Dynamin are corecruited at sites of phagosome formation in F‐actin—rich cups. In addition, NM23‐H1 was required for efficient phagocytosis. Together, our data demonstrate that NDK‐1/NME1 is an evolutionarily conserved element of successful phagocytosis.—Farkas, Z., Petric, M., Liu, X., Herit, F., Rajnavölgyi, É., Szondy, Z., Budai, Z., Orbán, T. I., Sándor, S., Mehta, A., Bajtay, Z., Kovács, T., Jung, S. Y., Afaq Shakir, M., Qin, J., Zhou, Z., Niedergang, F., Boissan, M., Takács‐Vellai, K. The nucleoside diphosphate kinase NDK‐1/NME1 promotes phagocytosis in concert with DYN‐1/dynamin. FASEB J. 33, 11606–11614 (2019). www.fasebj.org